RECREATIONAL RUNNER' STRATEGIES TO COPE WITH INJURY AND ILLNESS DURING MARATHON RACE PREPARATIONS: CROSS-SECTIONAL STUDY IN SWEDEN. Issue 4 (1st February 2017) - Gauffin, Håkan; Tillander, Bo; Dahlström, Örjan; Nyman, Henrik; Timpka, Toomas
Abstract : Background: Running is one of the most popular forms of physical exercise worldwide. It is therefore discomforting that pain and overuse injuries are common among recreational runners. The coping concept is used to denote conscious efforts to solve personal and interpersonal problems, and seeking to master, minimize or tolerate stress or conflict. Objective: To explore coping strategies associated with injury and illness management in runners. Design: Cross-sectional study based on an online survey. Setting: Recreational runners preparing for a marathon race. Patients (or Participants): Swedish recreational marathon runners. Interventions (or Assessment of Risk Factors): Age, sex, and coping strategies as measured by the Brief Cope instrument. Main Outcome Measurements: Episodes of injury or illness lasting at least three weeks during the past 12 months. Results: The response rate was 38% (317/833 runners). One out of five runners reported a pre-race health problem, with overuse injuries with gradual onset being the most frequent problem and the knee the most common localisation. No statistical differences between injured and non-injured runners were observed for any feature of the Brief Cope instrument. Runners having rested from running due to illness reported higher scores for the adaptive coping strategy active coping (p=0.020). They also reported lower scores for emotional support (p=0.020) and higher scores for the maladaptive coping strategy behavioural disengagement (p=0.041) than runners not having rested for illness. Conclusions: An association between active coping and rest due to illness was found among recreational marathon runners. Illness, usually having a sudden onset, seem to motivate marathon runners to rest more strongly than overuse injuries that normally have a gradual onset. The results indicate that health problems with gradual onset call for different approaches for behavioural interventions and prevention than those with sudden onset. Coping strategies among recreational runners warrant further research based on longitudinal study designs.